2010
DOI: 10.1021/jp103702d
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Hydrophobicity of Al Substrates by Chemical Surface Functionalization of Nano/Microstructures

Abstract: Superhydrophobic and self-cleaning surfaces may arise due to interplay between nano/microstructures at the solid surface and the chemical properties of the topmost monolayer. In the present work, those relationships were investigated by Al substrate modifications via chemical functionalization with trimethoxypropylsilane dipping, and coating with a thin perfluorinated layer. The effect of the nano/micromorphology on the superhydrophobicity and hysteresis was studied using two main approaches: (i) chemical etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 39 publications
3
59
0
Order By: Relevance
“…Surfaces with high Ti-OH concentrations will increase the work of adhesion and their CAHs. Our previous chemical studies on superhydrophobic surfaces also showed that the chemical heterogeneity on the surface strongly influences the final dynamic properties of a superhydrophobic surface [22,[45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfaces with high Ti-OH concentrations will increase the work of adhesion and their CAHs. Our previous chemical studies on superhydrophobic surfaces also showed that the chemical heterogeneity on the surface strongly influences the final dynamic properties of a superhydrophobic surface [22,[45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…By dicing [21] or laser photolithography [8] several hydrophobic micro structures were prepared; experimental results were compared with those of Wenzel-Cassie models. Superhydrophobic alumina films have been successfully developed on industrial aluminum foils by a simple anodization method following by chemical surface modification [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, several methods to obtain superhydrophobic surfaces have been developed due to great industrial interest in reducing flow resistance and fluidic drag [1], in repairable superomniphobic surfaces [2], in applications such as optical antireflection [3], corrosion protection [4], liquid transportation [5], biochemical separation [6], antibiofouling paints for boats, production of food packaging, inhibition of ice or snow adhesion [7,8], and self-cleaning surface properties [9]. Although easydewetting surfaces can be obtained in flat/smooth surfaces even with low contact angle [10], superhydrophobic surfaces with self-cleaning properties are usually characterized by exhibiting a very high Contact Angle (CA) and low Contact Angular Hysteresis [11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase surface roughness, there are two possibilities: the first one is thorough its generation on the substrate, such as by plasma etching [13], chemical etching [14] or embossing [15]; the second is thorough incorporation of a coating on the substrate, such as by electrospinning [16][17][18], chemical vapor deposition [19][20][21][22][23], lithography [24,25], dip coating [26,27], anodic aluminum oxide [9,28] [29,30] or physical vapor deposition (PVD) [15,31]. Hierarchical structures, i.e., with micro-and nanostructure, have been reported for stability of the superhydrophobic condition [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation